2012
DOI: 10.1007/s12264-012-1232-8
|View full text |Cite
|
Sign up to set email alerts
|

Planar cell polarity genes, Celsr1-3, in neural development

Abstract: flamingo is among the 'core' planar cell-polarity genes, protein of which belongs to a unique cadherin subfamily.In contrast to the classic cadherins, composed of several extracellular cadherin repeats, one transmembrane domain and one cytoplasmic segment linked to catenin binding, Drosophila Flamingo has seven transmembrane segments and a cytoplasmic tail with no catenin-binding sequence. In Drosophila, Flamingo has pleotropic roles in controlling epithelial polarity and neuronal morphogenesis. Three mammalia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 49 publications
1
24
0
Order By: Relevance
“…These data suggest that LSD1 and HDACs might associate with REST and other factors to create a repressive chromatin environment in untreated cells and that Corin blocks the removal of activating chromatin marks by LSD1 and HDACs at these regions. This hypothesis is exemplified by increased H3K27ac and H3K4me1 near predicted REST-binding sites at the CELSR1 locus ( Figure 2F), which encodes a regulator of neuronal differentiation and brain development (Boucherie et al, 2018;Feng et al, 2012), and a Corin-dependent increase in H3K27ac and H3K4me1 at REST sites on a global scale ( Figure S5D). In contrast, motifs bound by MAFG and NR3C family nuclear receptors are enriched in regions where Corin induces H3K27me3 ( Figure 2D).…”
Section: Chip-seq Reveals Global Alterations In H3k4me1- H3k27me3- mentioning
confidence: 86%
“…These data suggest that LSD1 and HDACs might associate with REST and other factors to create a repressive chromatin environment in untreated cells and that Corin blocks the removal of activating chromatin marks by LSD1 and HDACs at these regions. This hypothesis is exemplified by increased H3K27ac and H3K4me1 near predicted REST-binding sites at the CELSR1 locus ( Figure 2F), which encodes a regulator of neuronal differentiation and brain development (Boucherie et al, 2018;Feng et al, 2012), and a Corin-dependent increase in H3K27ac and H3K4me1 at REST sites on a global scale ( Figure S5D). In contrast, motifs bound by MAFG and NR3C family nuclear receptors are enriched in regions where Corin induces H3K27me3 ( Figure 2D).…”
Section: Chip-seq Reveals Global Alterations In H3k4me1- H3k27me3- mentioning
confidence: 86%
“…CELSR3 belongs to the flamingo subfamily of non-classic cadherins, which are defined by non-interaction with catenins and seven transmembrane domains (Feng et al, 2012). The protein encoded by this gene may be involved in the regulation of contact-dependent neurite outgrowth (Chai et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…CELSR1 is a developmentally regulated, neural‐specific gene involved in early embryogenesis. Recent work has shown that Celsr1 play important roles in neural development, such as in axon guidance and neuronal migration (Feng, Han, & Zhou, ). From a clinical point of view, coding mutations of CELSR1 were associated to neural tube defect both in mouse (Curtin et al, ) than in men (De Marco et al, ).…”
Section: Discussionmentioning
confidence: 99%